An Analysis of the Effect Compensation towards Employee Performance and Work Satisfaction of Employees of PT. Bank Rakyat Indonesia tbk. - Basso Yusril; Syamsu Alam; Maat Pono (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
This study aims to determine the effect of compensation on employee performance and work satisfaction at PT. Bank Rakyat Indonesia Tbk., Makassar Branch. The analytical method used is path analysis. Samples in this study were all amounting to 90 permanent employees of the company of PT Bank Rakyat Indonesia ( Persero ) Makassar Branch Office, Then, the size of the samples that can represent the population to be examined was 83 respondents with the t-test as a research hypothesis test. Based on the results of the research which have been done, it can be known partially that the independent variables, namely compensation, has a positive effect on employee performance and job satisfaction, the research results also prove that there is a positive influence of compensation on job satisfaction and employee performance of the employees of PT.Bank Rakyat Indonesia Persero Makassar Branch Office.